Analysis of the Effect of Remuneration on Performance of Civil Servants at Lampung Agriculture Training Center - Firmansyah Yunialfi Alfian; Ario Pratama (Proceeding International Conference on Information Technology and Business, 2017)
This Research was done at Lampung Agricultural Training Center as one of UPT under Agriculture Ministry and done the birocration reformation program that was remuneration given to employees. It was hoped that employees performance would increase. The aim of this study was to know and analyze the effect of Remuneration on Civil Servants Performance at Lampung Agricultural Training Center. The sample taking technique used was saturated sampling technique and used all population as the sample as 67 respondents. The data collecting method used was questionnaire. The independent variable was Remuneration and the dependent variable was Employee Performance. The data analysis included validity test, reliability test, classical assumption test and hypothesis test. The analysis result shows that Remuneration positively affected the Employee Performance. Keywords :Remuneration, and Employees Performance.